Detecção de mudanças paleoambientais no litoral do Rio Grande do Norte (RN) durante o Holoceno médio e superior - BATISTA, Edson José Louzada (Universidade Federal do Pará, 2017)
The vegetation dynamics during the Holocene on the coastal region of Rio Grande do Norte (RN) was characterized by mangrove establishment, expansion and contraction. The dynamics of this vegetation is mainly related to the sedimentary dynamics and to the relative sea level change (RSL) recorded for this period. During the last millennium, sedimentary process controlled the vegetation dynamics along stratigraphic profiles formed by sequences of active tidal channels, followed by abandonment. Therefore, based on grain size, sedimentary structures, pollen data, isotopic data (δ13C and δ15N), C/N ratio and 14C dating of the sedimentary organic matter of two cores (NAT 6 and NAT 8) sampled in the tidal plain, shows a paleoenvironmental model since mid- to late-Holocene (~7 k yr BP to modern), described by four facies associations: (A) estuary/channel, represented by massive sandy deposits (facies Sm) and mud deposition; (B) abandoned channel, represented by the wavy heterolithic bedding (facies Hw), lenticular heterolytic bedding (facies H1) and small intervals with massive sand (facies Sm); (C) active channel, corresponding to massive sandy deposits (facies Sm); and (D) low marsh (mangroves/herbaceous plain and palms), represented by clay deposits with lenticular heterolithic bedding (facies Hl). In this context, short-time (millennium/century) changes between mangroves and other associated vegetation in this region are not necessarily related to RSL or to the climatic changes (allocyclic process), but to the sedimentary dynamics (autocyclic process) must have controlled mainly the pollen assembly along the stratigraphic profiles studied.